NARASI HOAKS VAKSINASI COVID 19 PADA MEDIA BERITA (Studi Analisis Naratif Media Berita Tentang Vaksinasi Pada Laporan Utama Majalah Tempo) - Maria Tania (2022)
Hoax information about the Covid-19 vaccination is spreading on social media. The mass media caught the phenomenon and wrote it as news. Tempo is one of the media that writes news about the Covid-19 vaccination. This study aims to determine the form of narrative structure and storylines built in Tempo's coverage of the Covid-19 vaccination. The method used is qualitative with a narrative analysis research approach. The paradigm used is the narrative paradigm. The data analysis technique used is Vladimir Propp's narrative function analysis model and Todorov's narrative structure analysis modified by Nick Lacey to find the narrative structure written by Tempo. The results showed that the form of storytelling in Tempo magazine was not chronologically chronological, causing an understanding bias. The narrative form developed by Tempo in reporting appears in the form of news narration which has stages of continuity of disturbance and partial narration in its narrative structure.